Budaya Madrasah dan Masalah Perubahan - Jumadi (STAI Terpadu Yogyakarta, 2019)
Madrasah are educational institutions under the Ministry of Religion, which at this time many parents who send their children to Madrasah, it is evident that currently many Madrasas have rejected prospective students because the class has been fulfilled by prospective students. The number of parents entering their children into Madrasah is proof that Madrsah is able to turn students into better ones, for example lazy people become diligent, who used to be lazy to pray to be diligent in prayer and morality for the better, all of this they do because they wish him blessings. This is evident that Madrasah students, especially in Yogyakarta, don't hear news or talk about Madrasah students involved in brawls, drinking, drinking and others, this is because after they study Religion, they include Aqeedah, Worship, Morals, Koran, Hadith, Sharia and others and then practice it ( cognitive, affective and psychomotor). In the practice of worship, especially prayer, from the dhuha prayer and the dhuhur prayer in congregation at the school and implanted to perform prayers at home in congregation it is the cultivation of Islamic culture and also a change in Madrasah education. This is God's promise so that Madrasah students are spared from the case above. Madrasah culture is meant to make Madrasah as a tool for change for students who are invested solely in hopes of His blessings, changes that are solely because of Allah, so that the students will carry out their commands and abandon all restrictions, so that they are not affected negative in the Era of Industrial Revolution 4.0, but positively use it to preach to the path of goodness, that is maruf nahimungkar. Surely the prayer will prevent it from evil deeds and mischief. Therefore, Madrasas are obliged to cultivate the five-time obligatory prayer carried out in a timely manner in congregation.